Building a multipolar learning society through community learning pathways in a child-friendly village - Qowim, Muhammad; Santosa, Edy Yusuf Nur Samsu; Syafii, Ahmad; Yuyun, Yuyun (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2026)
Purpose – This study explains how differentiated community learning sites, embedded cultural and religious practices, and institutional networks combine to form a multipolar learning society in Karangdukuh Child-Friendly Village, Indonesia. Design/methodology/approach – A qualitative design with embedded units of analysis examined Sanggar Joglo Alit, Dojo Joglo Alit, and Pesantren Joglo Alit. Data from two focus group discussions, semi-structured interviews, participatory observations, and demographic, program, and institutional records were analysed through descriptive mapping, thematic analysis, and cross-unit comparison. Findings – The village profile indicates a need for accessible and varied learning support. The three units provide differentiated but overlapping pathways in arts and culture, sports, religious learning, literacy, and language enrichment. Mosque, heritage, and disability organizations extend learning through recurring social practices and specialized inclusive services. The emerging ecosystem is multipolar because educational functions, expertise, legitimacy, and resources are distributed across several relatively autonomous but complementary centres rather than controlled by a single provider. Research implications/limitations – The model offers a practical basis for coordinating community learning and localizing Sustainable Development Goals 3, 4, 10, 11, and 17. However, the study maps institutional architecture rather than measuring causal effects, participant trajectories, partnership durability, or longitudinal educational and health outcomes. Originality/value – The study conceptualizes multipolarity as functional differentiation and distributed support across community learning sites, extending learning-society research beyond school-centred and single-provider models.